Journal packing density of Library and Information Science journals published across Asia - Pandita, Ramesh; Singh, Shivendra (Malaysian Journal of Library and Information Science, 2022)
The purpose of the study is to compute the Journal Packing Density (JPD) i.e. the average research articles published in each volume or each issue of a research journal. Library and Information Science (LIS) journals published across Asia and indexed in Scopus during the period 2015 to 2019 were taken as samples. The study is based on secondary data retrieved from SCImago Journal and Country Ranking (SJCR), which includes the journals and country scientific indicators developed from the information contained in the Scopus database. In all, 14 LIS journals were identified from Asia. It was found that there are 51 sovereign nations in Asia, and 43 (84.31%) countries are actively undertaking research in LIS and only 8 (18.60%) countries are publishing LIS journals. India and Taiwan are the two leading countries in the region publishing 3 journals each. In all, 1558 articles were published by 14 LIS journals across Asia from 2015 through 2019 in 58 volumes with a JPD of 26.86 articles per journal per volume. Apart from these, research deficit in terms of journals and research articles has also been computed alongside a brief overview on how JPD of a journal can help in identifying the possibility of its predatory nature.